Accessibility of Low Income Earners to Home Financing: A Case Study in Kedah - Maamor, Selamah; Shuib, Mohd Sollehudin; Harun, Siti Latipah (International Journal of Economics and Financial Issues, 2016)
The purpose of this article is to examine the accessibility of low income earner to home financing facilities. This study involves 119 respondents who are low income earners in Kedah and have experience in applying and accessing home financing. Structured interview schedule was developed, pre-tested and used for collecting quantitative data for the study from the sample of low income group. Descriptive statistics were used for analysing quantitative data. Based on the finding, it shows that the lower income earners are looking for the house at the RM100, 000 with monthly payment of RM500 which is the maximum amount that they can afford to pay. In addition, they also really need an aid from the government in term of specific policies for low income earners to own affordable homes. With regards to level of information, individuals need clearer and accurate information on housing loans to ensure that they can make a right decision. Therefore, policy maker particularly government and banks need to consider these factors and provide the right tenant mixes, services and other facilities that are essential to ensure the lower income earner also have the equal opportunity to access home financing. Keywords: Home financing; low income earners; descriptive statistics; government intervention JEL Classifications: D6, G18, H2